The Invention of Computationally Plausible Knowledge Systems in the Upper Paleolithic - Klein, Sheldon (University of Wisconsin-Madison Department of Computer Sciences, 1985)
The problem of computing human behavior by rules can become intractable with large scale knowledge systems if the human brain, like a computer, is a finlte state automaton. The problem of making such computations at a pace fast enough for ordinary social interaction can be solved if appropriate constraints apply to the structure of those rules. There is evidence thak systems of such constraints were invented in the Upper Paleolithic, and were of sufficient power to guarantee that the time necessary for computation of behavior would increase only linearly with increases in the size and heterogeneity of world knowledge systems. Fundamentally, there was just one type of computational invention, capable of unifying the full range of human sensory domains, and consisting of an analogical reasoning method in combination with a global classification scheme. The invention may have been responsible for the elaboration of language and culture structures in a process of co-evolution. The encoding of the analogical mechanism in iconic visual imagery and myth structures may have given rise to the phenomenon of Shamanism. The theory is testable, and one of its implications is that the structuralism of Levi-Strauss has an empirical foundation.